The Small-Scale Dairy Value Chain Analysis: Challenges And Opportunities For Dairy Development In Mymensingh District Of Bangladesh (SAARC Journal of Agriculture, 2020)
This study examined the prevailing dairy value chain based on primary data collected from 70 small-scale milk producers of Mymensingh district of Bangladesh. The total cost and net return per month per cow were Tk. 4024.30 and Tk. 3165.70, respectively. The net value additions of Tk. 2091.42, Tk. 495.00, Tk. 655.00, Tk. 503.25, Tk. 309.70 were estimated for milk producers, collectors, Faria, Bepari and retailers respectively. Different actors spent highest marketing cost ranged from Tk.49 to Tk.80 for transportation compared to other marketing functions. Actors mostly dependent on the on-going market prices for setting price of milk in the value chain. A value chain map was developed showing the relationships and linkages among value chain actors of small-scale dairy. The study identified some critical factors for successful dairy marketing. The factors were understanding consumer behaviour, technology and transportation, improved business relationships, reduced transaction costs, and improved information flow, and organized market structure. Milk producer’s share in consumers’ price was highest for channel- I followed by channel- V. Expensive, inadequate, low quality feed, lack of grazing land, green grass, inadequate capital, knowledge about cost of production, weak extension services, high fees and unavailability of veterinary doctors, were some of the major problems of milk producers. Supply of adequate feed at subsidized price, ensuring easy access to institutional credit at a lower interest rate, adequate medicine and veterinary services, allocation of khas land for producing fodder/grass, were suggested to solve the problems.SAARC J. Agri., 17(2): 213-226 (2019)